Integratıon of modern methodologıes wıth PMO in the management of ınvestment projects - Babayev, І.; Quluzada, S.; Бабаєв, І. А.; Кулузада, С. (Харківський національний автомобільно-дорожній університет, 2025)
The integration of modern project management methodologies within Project Management Offices (PMOs) is crucial for enhancing investment project management. Traditional PMO structures often struggle to meet the demands of agility, efficiency, and risk mitigation required in dynamic environments. This study examines the role of PMOs in investment projects, particularly in infrastructure, energy, and technology, highlighting the challenges posed by uncertain market conditions, regulatory constraints, and technological disruptions. To address these challenges, organizations are increasingly integrating Agile, Lean, Scrum, Kanban, and hybrid methodologies within the PMO framework. These methodologies improve project success rates by optimizing resource allocation, enhancing stakeholder engagement, and facilitating data-driven decision-making. Agile PMO structures, in particular, enable iterative planning, rapid adaptation, and effective risk management, making them well-suited for investment projects facing high uncertainty. Despite the growing interest in modern methodologies, challenges remain in harmonizing these approaches within PMO structures. This study explores key opportunities, obstacles, and success factors associated with such integration. It highlights the importance of fostering an agile mindset within project teams and aligning PMO functions with strategic organizational goals. The findings suggest that integrating contemporary methodologies into PMO frameworks enhances project governance, improves efficiency, and increases competitiveness. The study also emphasizes the role of digital tools and sustainability principles in modern investment project management. By adopting innovative, flexible, and structured approaches, organizations can maximize value creation, optimize decision-making, and ensure long-term project success.
Інтеграція сучасних методологій з PMO в управлінні інвестиційними проєктами
Keywords: Project Management Office; investment projects; modern methodologies; systematic management approaches; success factors; Офіс управління проєктами; інвестиційні проєкти; сучасні методології; системні підходи до управління; фактори успіху; 65.012.4:658.5; 10.30977/ЕТК.2225-2304.2025.45.171